1996
DOI: 10.1111/j.1365-2648.1996.tb02664.x
|View full text |Cite
|
Sign up to set email alerts
|

Adjustment and social behaviour in older adults with chronic obstructive pulmonary disease: the family's perspective

Abstract: This study employed secondary data analysis to explore family perceptions of adjustment and social behaviour in older adults (n = 51) with chronic obstructive pulmonary disease (COPD) and their relationship to published norms and patient self-report. According to the Katz Adjustment Scale for Relatives, these COPD patients had significantly higher levels of belligerence, negativism, helplessness, withdrawal, psychopathology, nervousness and confusion than reports from relatives of older adults from the general… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0
1

Year Published

1999
1999
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 31 publications
2
33
0
1
Order By: Relevance
“…The partners’ relationship satisfaction was found to predict the partners’ supportive behavior. Studies have shown that the well‐being of family members is inherently important and can influence the family’s ability to provide the support necessary for patient coping and disease management (Leidy & Traver, 1996; Sandhu, 1986; Siegrist & Junge, 1990). The patients’ illness is likely to affect the partners’ family roles and responsibilities, social activities, sleep, and sexual functioning (Bergs, 2002; Sexton & Munro, 1985).…”
Section: Discussionmentioning
confidence: 99%
“…The partners’ relationship satisfaction was found to predict the partners’ supportive behavior. Studies have shown that the well‐being of family members is inherently important and can influence the family’s ability to provide the support necessary for patient coping and disease management (Leidy & Traver, 1996; Sandhu, 1986; Siegrist & Junge, 1990). The patients’ illness is likely to affect the partners’ family roles and responsibilities, social activities, sleep, and sexual functioning (Bergs, 2002; Sexton & Munro, 1985).…”
Section: Discussionmentioning
confidence: 99%
“…The KAS-R has been shown to approximate clinical judgment and has discriminated between well-adjusted patients and poorly adjusted patients 27,28. It has also been used successfully in studies of patients with COPD 2931. Two subscales were used to validate the FPI-SF: performance of socially expected activities (16 items, α = 0.88) and free-time activities (22 items, α = 0.85).…”
Section: Methodsmentioning
confidence: 99%
“…It was important for the spouse to have a part-time job in order to reduce both the isolation and the economic burden (Brewin, 2004). When studying the family's perspective on adjustment and social behaviour of older adults with severe COPD, it was clear that the caregivers were dissatisfied with leisure activities, and that relatives of chronically ill men experienced more dissatisfaction with socially expected activity performance than did relatives of chronically ill women (Leidy and Traver, 1996). As the COPD progresses, the relationship is affected, with a decrease in shared activities and less time being spent together as a couple (Simpson et al, 2010).…”
Section: Introductionmentioning
confidence: 99%